Clinicopathological Analysis of Ovarian Tumours at Birendra Military Hospital - Khatri, R (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Ovarian cancer is the second most common genital tract malignancy accounting for 25% gynaecological malignancy. This study was conducted to determine the incidence, epidemiological factors and clinical presentation of different types of ovarian tumours their correlation with histopathology. Methods: This is a descriptive study conducted in Birendra Military Hospital over a period of 2 years. The case records of all the patients with ovarian tumur was analyzed. Results: Of the total of 135 adnexal masses cases 100 (74.07%) were found to be histologically proven ovarian tumour out of which 35 were non neoplastic conditions. Benign tumours comprised of 68 (68%) and 32 (32%) were malignant and borderline.Mature cystic teratoma 28 (75%) was the commonest benign tumour, whereas serous cystadenocarcinoma 13 (64.3%) were commonest malignancy. Age varying from 2.5 yrs. To 70 yrs. Smallest tumour size was 2.5 cm. largest was 40 cm. Commonest symptom was abdominal discomfort and most common sign was abdominal lump. Malignancy usually presented with ascites especially epithelial ovarian tumours. Germ cell tumour was observed in younger age group in earlier stage. Conclusion: The commonest ovarian tumor was epithelial followed by germcell. Mature cystic teratoma was the most common benign tumour and malignant was serous cyst adenocarcinoma. Epithelial ovarian tumour prevalent in perimenopausal and postmenopausal age group whereas germ cell in earlier age. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6446 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 26-31